2022
DOI: 10.17275/per.22.25.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning with Mind Mapping in the Development of Social Skills of Children

Abstract: During the social process of the preschool period, the aim is to enable children to gain social skills which will help them to adapt to the classroom, and prepare them for their social life. Benefiting from cooperative teaching methods in the development of social skills supports children's interactions with each other. The carrying out of group work with new and different approaches, which incorporate collaboration in the activities, is significant for the development of the social skills and peer interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…Collaborative learning can have a positive impact on students' social skills (Polat, 2022). In line with Law's research (2017) which in his research has also proven that collaborative learning has a positive impact on social learning.…”
Section: Resultssupporting
confidence: 63%
“…Collaborative learning can have a positive impact on students' social skills (Polat, 2022). In line with Law's research (2017) which in his research has also proven that collaborative learning has a positive impact on social learning.…”
Section: Resultssupporting
confidence: 63%
“…Particularly for our work, MM also serves a unique purpose in mixing with CL, as it has been suggested that mind maps can facilitate CL [71]. MM can serve as a shared visual language for learners to exchange ideas, negotiate meanings, and co-construct knowledge when used in group activities [69], [72], [73].…”
Section: Mind Mappingmentioning
confidence: 99%
“…53 Mind mapping practiced in collaborative learning shows more effective success than traditional techniques. 54 Collaborative learning strategies using mind mapping can help students understand a second language better. 55 Mind mapping is a creative tool, which keeps students engaged in collaborative learning and active knowledge representation can be realized.…”
Section: Mind Mapping Compiled By Students Collaborativelymentioning
confidence: 99%